Propuesta de diseño de un producto de protección auditiva impermeable, para la práctica de natación, en usuarios con Tinnitus crónico - Cancellier Almeida, Giuliana Manuela (2020)
A person suffering from tinnitus, perceives sounds that are not caused by an external source. This happens because the brain misinterprets the electrical signals emitted by the cells of the inner ear. Therefore, those who suffer from it live under incessant noise that is impossible to control. The type and intensity of this noise varies depending on the person. Tinnitus conditions the quality of life, since they must live cautiously in situations that may expose or intensify their condition.Koi, is a proposal that seeks to protect the hearing health of people who suffer from tinnitus caused by chronic ear pathology, by creating a waterproof and moldable hearing protection product, which allows the practice of swimming to benefit from its therapeutic effects without concern. In addition, it focuses on calming the mind, eliminating stress and anxiety generated by this psycho- sensory phenomenon that has no cure, through the predictive reproduction of relaxing Zen music that helps to mask tinnitus. So, this accessory is designed for everyday use thanks to its versatility. This project places the user at the center of the entire design process, examining their needs and behaviors that will benefit from the resulting solutions. This process is made up of tools in order to generate new modes of interaction. Also, it seeks to apply lessons from nature and unveil new responses to develop a healthy and sustainable product.